Ineffectiveness of colistin monotherapy in treating carbapenem-resistant Acinetobacter baumannii Pneumonia: A retrospective single-center cohort study - Cheon-Hoo Jeon; Si-Ho Kim; Hyoung‑Tae Kim; Kyoung-Jin Park; Yu Mi Wi (Elsevier, 2024)
Background: Acinetobacter baumannii, a common carbapenem-resistant gram-negative bacillus, usually causes nosocomial infections. Colistin has been used for carbapenem-resistant A. baumannii (CRAB) infections; however, only a few studies have evaluated colistin as a treatment option compared to appropriate controls. We investigated the effectiveness of colistin monotherapy in treating CRAB pneumonia compared to those treated without an active drug. Methods: Adult patients (≥ 18 years) with CRAB isolated from respiratory specimens were screened from September 2017 to August 2022. Only patients with pneumonia treated with colistin monotherapy (colistin group) were included and compared to those without any active antibiotics (no active antibiotics [NAA] group). The primary and secondary outcomes were 30-day all-cause mortality and acute kidney injury within 30 days. The inverse probability of the treatment-weighted Cox proportional hazard model was used to compare mortality between groups. Results: Among the 826 adult patients with CRAB in their respiratory specimens, 45 and 123 patients were included in the colistin and NAA groups, respectively. Most of the CRAB pneumonia (91.1%) cases were hospital-acquired pneumonia. The 30-day all-cause mortality rates in the colistin and NAA groups were 58.3% and 56.1%, respectively, and no difference was observed after adjustments (adjusted hazard ratio, 0.74; 95% CI, 0.47-1.17). The incidence of acute kidney injury was higher in the colistin group (65.3%) compared to the NAA group (39.0%) (P = 0.143). Conclusions: Colistin monotherapy did not significantly improve treatment outcomes for CRAB pneumonia. The development and evaluation of new antimicrobials for CRAB pneumonia should be advocated in clinical practice.